2011
DOI: 10.1177/1753425910396252
|View full text |Cite
|
Sign up to set email alerts
|

Complement and non-complement activating functions of C1q: A prototypical innate immune molecule

Abstract: C1q is a versatile innate immune molecule that serves as the initiation subcomponent of the classical complement pathway. In addition, it is also a potent pattern recognition molecule, the versatility of which has fuelled its functional flexibility. C1q recognises an array of self, non-self and altered-self ligands. The broad-spectrum ligand-binding potential of C1q is facilitated by the modular organisation of the heterotrimeric globular head region, its ability to change its conformation in a very subtle way… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
99
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(101 citation statements)
references
References 135 publications
2
99
0
Order By: Relevance
“…Because both gC1q receptors and LAIR-1 are present on freshly isolated monocytes and gC1q has been shown to engage gC1q cellular receptors directly (1,23,24), it is possible that binding of gC1q to gC1q receptors contributes to the avidity of the C1q interaction with LAIR-1 and to the cross-linking of LAIR-1. Notwithstanding, the inhibitory activity prompted by anti-LAIR-1 antibodies that promote LAIR-1 cross-linking indicates that engagement of gC1q is not required for LAIR-1 activation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because both gC1q receptors and LAIR-1 are present on freshly isolated monocytes and gC1q has been shown to engage gC1q cellular receptors directly (1,23,24), it is possible that binding of gC1q to gC1q receptors contributes to the avidity of the C1q interaction with LAIR-1 and to the cross-linking of LAIR-1. Notwithstanding, the inhibitory activity prompted by anti-LAIR-1 antibodies that promote LAIR-1 cross-linking indicates that engagement of gC1q is not required for LAIR-1 activation.…”
Section: Discussionmentioning
confidence: 99%
“…These include facilitating phagocytosis and regulating cellular differentiation, survival, migration, and cytokine secretion (1)(2)(3)(4)(5). An immunosuppressive role for C1q is supported by the high frequency of C1q-deficient individuals who develop systemic lupus erythematosus (SLE) (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…C1q is well known to activate the classical pathway and to act as a defense molecule favoring the removal of infectious agents, apoptotic cells, and immune complexes (16). In Significance C1q is a well-known initiator of the complement classical pathway and interacts with several immune and nonimmune cells inducing complement activation-independent functions.…”
Section: Complement | Vasculogenesis | Animal Modelsmentioning
confidence: 99%
“…In addition, we found that the expression of the 11 differentially expressed serum proteins (C1QB, C1QC, ANXA1, LYZ, CP, ACT, ZG16B, S100A8, S100A9, SERPINA4, and LUM) was associated with the RCC tumor stage and grade. Functionally, C1QB and C1QC are complement subcomponent subunits (16) and are related to antibody-dependent and -independent immune responses in the human body (17). They are able to induce apoptosis of prostate cancer cells by targeting the tumor suppressor WWOX and hampering cell adhesion via a mechanism which is still unknown (18).…”
Section: Discussionmentioning
confidence: 99%